Surgical Therapeutic Strategy of Transdural Nerve Root Herniation during Anterior Lumbar Interbody Fusion: Report of Two Cases - Yong Jae Lee; Yong Ahn (Journal of Minimally Invasive Spine Surgery and Technique, 2018)
We report two cases of transdural nerve root herniation caused by incidental dural tear during anterior lumbar interbody fusion. We also describe how these unexpected complications were managed. Two patients suffered from degenerative spondylolisthesis and foraminal stenosis with a redundant dural sac. In these patients, the dural tears occurred during anterior discectomy and the nerve roots subsequently herniated outward because of intradural pressure. The herniated neural tissues were restored via a posterior transdural approach. There is always the possibility of a dural tear with nerve root herniation during surgery employing an anterior lumbar approach. If this occurs, we should be aware of the difficulty in repairing the dura from this approach. We should also keep in mind that adequate repair of it is important to avoid related postoperative complication.